Predictors of poor maternal and perinatal outcome among singleton maternal delivery referral cases to the obstetrics unit of a tertiary health facility in Port Harcourt, Nigeria - Awoyesuku, Peter A.; Mac Pepple, Dagogo A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The high maternal and perinatal mortality rates in Nigeria continue to be issues of concern. That antenatal care improves both perinatal and maternal outcomes is now well established. The study seeks to identify the predictors of poor maternal and perinatal outcome among singleton maternal delivery cases referred to Rivers State University Teaching Hospital (RSUTH). Methods: A longitudinal study was employed; the patients referred to RSUTH were followed up to ascertain maternal and neonatal outcomes. A sample size of 460 was used. Selection of cases was done by systematic sampling. Data obtained in the study were demographic, obstetric and perinatal findings. Maternal and perinatal outcome were dichotomized into poor and good outcomes. Bivariate and multivariate analyses were performed using SPSS version 20.0. Results: A total of 460 cases were recruited. The mean age±SD was 28.7±4.6 years. There was poor maternal outcome in 65 (14.1%) and poor perinatal outcome in 291 (63.3%). There was one maternal death (rate 0.2%), perinatal mortality rate was 26.5%, low birth-weight rate was 6.3% and asphyxia rate was 23.3%. There is an association of multiparity and unbooked status with poor maternal outcome, while poor perinatal outcome was influenced by unbooked status. Conclusions: Perinatal and maternal mortality were high amongst all referral cases. There is a positive correlation of multiparity with poor maternal outcome and between unbooked status and an increased risk of both maternal and perinatal adverse outcomes.